Association of Pestalotiopsis Guepinii (DESM.) Stay. with Bipolaris Leaf Blight (BpLB) Infected Wheat Leaves-A new Record (Journal of Bangladesh Academy of Sciences, 2016)
Pestalotiopsis guepinii (Desm.) Stay an anamorphic fungus belonging to the class Celomycetes was isolated from Bipolaris leaf blight (BpLB) infected wheat leaf of two wheat varieties namely, Balaka and Saurab during the period of February to March, 2011. Association of Pestalotiopsis guepinii with wheat is a new record.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 1, 87-90, 2016